Resilient Cities urban nutrition profile: Bangladesh - Margolies, Amy; Choo, Esther; Singh, Nishmeet; Parvin, Aklima; Ruel, Marie T.; Olney, Deanna K. (International Food Policy Research Institute, 2024)
Urban-rural disparities in undernutrition in children under five have dissipated. Stunting declined from 2014 to 2022 in both urban and rural areas, but more so in rural areas, leading to comparable rates of stunting in urban and rural areas (22 percent, 24 percent). Wasting remains “high” (according to the World Health Organization) in both urban and rural areas (11 percent). The prevalence of child overweight is low but increasing, especially in Dhaka. Vitamin A deficiency affects half of children under five. Vitamin D and iron deficiencies are higher in urban areas, with zinc and iodine deficiencies more prevalent in rural areas. Urban and rural diets lack fruits and vegetables. A third of urban households have inadequate caloric intake. The cost of a healthy diet increased from $3.03 to $3.64 per person per day from 2017– 2022 and the percentage of the population unable to afford a healthy diet fell from 65 to 48 percent. Currently, 82 million people are unable to afford a healthy diet in the country. The diet diversity of young children has improved since 2011, but gains were seen mostly in rural areas. The percentage of all children fed the minimum meal frequency dropped by 20 percentage points from 2017 to 2022. Urban informal settlements are a concern – children have higher rates of stunting, lower dietary diversity, and higher prevalence of micronutrient deficiencies compared to other urban children. Overweight and obesity in urban adults is a critical problem. More urban women (48 percent) are overweight compared to rural women (35 percent); the same is true for urban men (29 percent) compared to 17 percent for rural men. Some urban nutrition interventions to tackle child undernutrition are being implemented, but few have been rigorously evaluated. Data on urban food environments (FEs) is becoming more available, but there are gaps in knowledge, particularly on the design and evaluation of interventions to counter the influence of the country’s increasingly obesogenic urban FE. National policies include targeted actions to improve urban diets and nutrition. More could be done, however, to improve the healthiness and safety of FEs, leverage social protection programs for the urban poor to make healthy diets more affordable, and to implement double-duty actions to address all forms of malnutrition.